Identification of minor distillate components of sunflower oil refining - E. A. Butina; E. O. Gerasimenko; I. A. Dubrovskaya; S. A. Kalmanovich; E. B. Krasavtsev (Новые технологии, 2017)
The research is devoted to the identification and investigation of the chemical composition of the minor components of distillation refining cuts of sunflower oils obtained by large Russian oil refineries. Minor components of the nonsaponifying fraction have been identified, among which the nitrogen containing substances, hydrocarbons and oxidation products are found. These components have varying degrees of volatility, cause a dark color of the distillates and have a negative effect on the efficiency of the processes of dividing the distillate cuts into constituent components. On the basis of the analysis of the results obtained, it’s been concluded that for effective processing of distillation cuts in order to obtain purified fatty acids and concentrates of valuable substances of the nonsaponifiable fraction, a process of preliminary removal of undesirable minor components should be carried out.